Promoting circular economy and sustainable construction practices : investigating the integration of waste upcycling for a greener future, with a focus on eggshell and eggshell membrane utilization - Brink, Deon (University of Pretoria, 2024)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2023.